Serotonin-Dopamine Interaction : Experimental Evidence and Therapeutic Relevance - Di Giovanni, Giuseppe; Di Matteo, Vincenzo; Esposito, Ennio; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2008)
This book provides a unique and timely multidisciplinary synthesis of our current knowledge of the anatomy, pharmacology, physiology and behavioral data of the serotonin (5-HT)-dopamine (DA) interactions. Central serotonergic and dopaminergic systems play a critical role in the regulation of normal and abnormal behaviors. Moreover, recent evidence suggests that the dysfunction of the DA and 5-HT neurotransmitter systems contribute to various mental disorders including depression, schizophrenia, drug addiction and Parkinson?s disease. This extremely important topic is of wide interest within th.
Text in English.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Serotonin -- Physiological effect -- Research; Serotonin -- Therapeutic use -- Research; Serotonin -- Antagonists -- Research; Dopamine -- Physiological effect -- Research; Dopamine -- Therapeutic use -- Research; Dopamine -- Agonists -- Research; Neurotransmitters -- Research; Neurochemistry; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Dopamine -- physiology; Serotonin -- physiology; Dopamine Agonists; Drug Interactions; Serotonin Receptor Agonists; Neurochemistry; Electronic books